Visuospatial Working Memory in ADHD Patients, Unaffected Siblings, and Healthy Controls. (May 2014) - van Ewijk, Hanneke; Heslenfeld, Dirk J.; Luman, Marjolein; Rommelse, Nanda N.; Hartman, Catharina A.; Hoekstra, Pieter; Franke, Barbara; Buitelaar, Jan K.; Oosterlaan, Jaap
Objective: The aim of this study was to (a) test the usefulness of visuospatial working memory (VSWM) as an endophenotype for ADHD and (b) study the developmental trajectory of VSWM in ADHD.Method: A total of 110 ADHD patients, 60 unaffected siblings, and 109 controls, aged 8 to 29 years, were assessed on VSWM functioning. Multilevel analyses were carried out to account for the correlation between measurements within families.Results: ADHD patients showed impaired VSWM performance compared with unaffected siblings and controls, with comparable performance between unaffected siblings and controls. Impaired VSWM in ADHD patients was not more pronounced on higher memory loads, signifying executive rather than storage deficits as an underlying mechanism. ADHD patients, unaffected siblings, and controls showed parallel developmental trajectories of VSWM.Conclusion: Current findings question the usefulness of VSWM as a neurocognitive endophenotype for ADHD and provide unique insights into the developmental trajectory of VSWM in ADHD.